p60c-src is complexed with a cellular protein in subcellular compartments involved in exocytosis (The Rockefeller University Press, 1988)
We found high levels of the c-src gene product in neuroendocrine tissues from adult animals. To understand the role of this proto- oncogene product, the subcellular localization of p60c-src was studied in neuroendocrine tissue from adrenal medulla. The results indicate that p60c-src was highly enriched in chromaffin granule membranes, in stable association with a protein of 38 kD. The complex with the 38-kD protein was also detected in brain, a tissue known to carry high levels of p60c-src. The 38-kD protein is not calpactin I, II, or synaptophysin. Comparison of its peptide map showed a high degree of conservation among the different species and tissues examined. The interaction between p60c-src and the 38-kD protein involves disulphide bonds that are stable even when the cell fractionation is performed in the presence of a reducing agent. Since the presence of disulphide bonds among cytoplasmic proteins is very unlikely, the possibility of a noncovalent association between p60c-src and the 38-kD protein in vivo is discussed. The 38-kD protein may be involved in a function of p60c- src related to secretory organelles.